2007
DOI: 10.1002/jcp.20994
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptors in colon carcinoma tissues and colon tumoral cell lines: Focus on the A3 adenosine subtype

Abstract: Adenosine may affect several pathophysiological processes, including cellular proliferation, through interaction with A(1), A(2A), A(2B), and A(3) receptors. In this study we characterized adenosine receptors in human colon cancer tissues and in colon cancer cell lines Caco2, DLD1, HT29. mRNA of all adenosine subtypes was detected in cancer tissues and cell lines. At a protein levels low amount of A(1), A(2A), and A(2B) receptors were detected, whilst the A(3) was the most abundant subtype in both cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 44 publications
(65 reference statements)
8
87
0
1
Order By: Relevance
“…The presence of adenosine receptors was recently investigated in HT29 cells, which express all four adenosine receptor subtypes. In particular, A 1 receptors are present with 32 Ϯ 4 fmol/mg of protein, A 2A receptors with 49 Ϯ 4 fmol/mg of protein, A 2B receptors with 52 Ϯ 4 fmol/mg of protein, and A 3 receptors with 257 Ϯ 22 fmol/mg of protein (Gessi et al, 2007). To evaluate whether A 3 receptors may have a functional role in HIF-1␣ protein expression under hypoxic conditions, we tested the effect of increasing concentrations (10-1000 nM) of the high-affinity A 3 receptor agonist Cl-IB-MECA (Table 1) (Merighi et al, 2005b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of adenosine receptors was recently investigated in HT29 cells, which express all four adenosine receptor subtypes. In particular, A 1 receptors are present with 32 Ϯ 4 fmol/mg of protein, A 2A receptors with 49 Ϯ 4 fmol/mg of protein, A 2B receptors with 52 Ϯ 4 fmol/mg of protein, and A 3 receptors with 257 Ϯ 22 fmol/mg of protein (Gessi et al, 2007). To evaluate whether A 3 receptors may have a functional role in HIF-1␣ protein expression under hypoxic conditions, we tested the effect of increasing concentrations (10-1000 nM) of the high-affinity A 3 receptor agonist Cl-IB-MECA (Table 1) (Merighi et al, 2005b).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, very high A 3 AR protein expression was observed in a variety of cancer cell lines (Gessi et al, , 2007Merighi et al, 2001Merighi et al, , 2009Suh et al, 2001;Morello et al, 2009;Jajoo et al, 2009;Cohen et al, 2011;Hofer et al, 2011;Varani et al, 2011aVarani et al, , 2013Kanno et al, 2012;Nogi et al, 2012;Kamiya et al, 2012;Otsuki et al, 2012;Vincenzi et al, 2012;Nagaya et al, 2013;Sakowicz-Burkiewicz et al, 2013;Madi et al, 2013) and in cancer tissues (Gessi et al, 2004a;Madi et al, 2004;Bar-Yehuda et al, 2008;Varani et al, 2011a), thus suggesting a role for this subtype as a tumoral marker.…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…Both pro-and antiapoptotic as well as pro-and antiproliferative effects have been reported depending on the level of receptor activation (Jacobson, 1998;Merighi et al, 2005b;Gessi et al, 2007;Kim et al, 2010;Taliani et al, 2010;Varani et al, 2011a;Sakowicz-Burkiewicz et al, 2013). At first, telomerase activity inhibition and cytostatic effects were observed in tumor cells (Fishman et al, 2000(Fishman et al, , 2001.…”
Section: H Cancermentioning
confidence: 99%
“…[107,108] Other studies indicate that A 2B adenosine receptor is highly expressed also in oral squamous carcinoma cell lines, as well as in human oral carcinoma tissues, where its expression is correlated with those of HIF-1. [109] Studies by Gessi et al [110] demonstrate that in colon cancer cells, although at the mRNA levels A 2B receptor is more expressed than A 1 , A 2A and A 3 , the density of A 3 receptors is the highest among the adenosine receptor subtypes. Later, other studies have demonstrated that the adenosine A 2B receptor is up-regulated in colorectal carcinoma tissues and colon cancer cell lines compared with normal colorectal mucosa under hypoxic conditions.…”
Section: A 2b Receptor and Tumor Stromamentioning
confidence: 99%
“…[113] Moreover, stimulation of A 2B receptor with a non-selective adenosine analog NECA induces apoptosis in ovarian cancer cells. [114] Nonetheless,while a number of studies demonstrate that stimulation of A 2B adenosine receptor in some cancer cell types promotes proliferation, whereby knockdown or pharmacological inhibition of this receptor reduces tumor cell growth and promotes apoptosis, [107][108][109][110][111] opposite results have been also described. [112,113] The discrepancy might likely depend on the cancer cell types, the expression levels of this receptor on tumor cells and the selectivity and/or concentrations of pharmacological tools used in the experimental settings.…”
Section: A 2b Receptor and Tumor Stromamentioning
confidence: 99%